Microbial Glycoside Hydrolases in the First Year of Life: An Analysis Review on Their Presence and Importance in Infant Gut - Ioannou, Athanasia; Knol, Jan; Belzer, Clara (Frontiers in Microbiology, 2021)
The first year of life is a crucial period during which the composition and functionality of the gut microbiota develop to stabilize and resemble that of adults. Throughout this process, the gut microbiota has been found to contribute to the maturation of the immune system, in gastrointestinal physiology, in cognitive advancement and in metabolic regulation. Breastfeeding, the ‘golden standard of infant nutrition’, is a cornerstone during this period, not only for its direct effect but also due to its indirect effect through the modulation of gut microbiota. Human milk is known to contain indigestible carbohydrates, termed human milk oligosaccharides, that are utilized by intestinal microorganisms. Bacteria that degrade human milk oligosaccharides like Bifidobacterium longum subsp. infantis, Bifidobacterium bifidum and Bifidobacterium breve dominate the infant gut microbiota during breastfeeding. A number of carbohydrate active enzymes have been found and identified in the infant gut, thus supporting the theory that these bacteria are able to degrade human milk oligosaccharides. It is suggested that via resource-sharing and cross-feeding, the initial utilization of human milk oligosaccharides drives the interplay within the intestinal microbial community. This is of pronounced importance since these communities promote healthy development and serve as a platform for the adult microbiome. The emerging production and accessibility of metagenomic data make it increasingly possible to unravel the metabolic capacity of entire ecosystems. Such insights can increase understanding of how the gut microbiota in infants is formed and makes it a possible target to support healthy growth. In this manuscript, we discuss the presence and function of carbohydrate active enzymes relevant to human milk oligosaccharide utilization in the first year of life, based on publicly available metagenomic data. We compare the enzyme profiles of breastfed children throughout the first year of life to those of formula-fed infants.